New South Wales Australia 1:50 000 topographic series. 8525-II & III, Mount Kosciusko - Central Mapping Authority of New South Wales (Bathurst, [N.S.W.] : C.M.A., 1982)
Map showing topographic, cadastral and local government information. Relief shown by contours and spot heights
Compilation date determined from field revision 1980
Panel title
Keywords: Kosciuszko, Mount, Region (N.S.W.) -- Maps